2021
DOI: 10.1128/spectrum.00930-21
|View full text |Cite
|
Sign up to set email alerts
|

Eptesicus fuscus Orthorubulavirus, a Close Relative of Human Parainfluenza Virus 4, Discovered in a Bat in South Dakota

Abstract: Bats are a reservoir of large numbers of viruses. Among bat-borne zoonotic viruses, members of Coronaviridae and Paramyxoviridae have had the largest impact on human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Additionally, during this study, Eptesicus fuscus, which was preyed upon by cats multiple times, was found to potentially harbour paramyxoviruses closely related to Human Parainfluenza Virus 4, thereby increasing its zoonotic potential (Hause et al 2021). Moreover, domestic cats are susceptible (Westbury et al 1996), and may potentially transmit Hendra virus, a bat-borne Henipavirus mostly found in Australia, to horses (Williamson et al 1998).…”
Section: Spillover Of Bat-associated Zoonotic Pathogens To Catsmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, during this study, Eptesicus fuscus, which was preyed upon by cats multiple times, was found to potentially harbour paramyxoviruses closely related to Human Parainfluenza Virus 4, thereby increasing its zoonotic potential (Hause et al 2021). Moreover, domestic cats are susceptible (Westbury et al 1996), and may potentially transmit Hendra virus, a bat-borne Henipavirus mostly found in Australia, to horses (Williamson et al 1998).…”
Section: Spillover Of Bat-associated Zoonotic Pathogens To Catsmentioning
confidence: 79%
“…Additionally, during this study, Eptesicus fuscus , which was preyed upon by cats multiple times, was found to potentially harbour paramyxoviruses closely related to Human Parainfluenza Virus 4, thereby increasing its zoonotic potential (Hause et al. 2021).…”
Section: Spillover Of Bat‐associated Zoonotic Pathogens To Catsmentioning
confidence: 88%
“…HPIV-2 and 4 are the causal agents of respiratory disease and can lead to severe outcomes [ 67 ]. Considering the recent identification of a close relative of parainfluenza virus 4 (another virus of human health concern, Orthorubulavirus ) in Eptesicus bats [ 68 ], bats may harbor the common ancestor of diverse parainfluenza viruses circulating in humans. In R. aegyptiacus , our study revealed a molluscum contagiosum-like poxvirus (PoxV-1A) related to the human MCV, which can persist for weeks or even years instead of causing acute disease [ 69 – 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The insectivorous E. fuscus is synanthropic and frequently roosts in human-made structures, leading to frequent interaction with humans. Besides being a known reservoir for the rabies virus, E. fuscus harbors many viruses that may pose zoonotic risks [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%